Analysis of Factors Causing the Incident of Phlebitis in Efforts to Increase Patient Safety at Nahdlatul Ulama Permata Hospital Lumajang - Hafizh Auliyan Sodali; Sentot Imam Suprapto; Agustin Widyowati (Universitas STRADA Indonesia, 2025)
Phlebitis is an inflammatory of the vein walls caused by medical procedures in hospitals. The purposes of this research is to explore the factors causing the incidence of phlebitis at Nahdlatul Ulama Permata Lumajang hospital. This research uses a qualitative design with a descriptive approach. Data collection was carried out through in-depth interviews, observation and documentation with 30 respondens of emergency room and inpatient nurses. Data analysis was carried out descriptively using triangulation and analysis methods. The results of the analysis revealed that the factors causing the high incidence of phlebitis were lack of adaptation and master of the tools, lack of controlling and discipline of nurses in implementing their understanding. So it is hoped that agencies can carry out training and evaluate the type of infusion abocath that will be used, and improve the quality of supervision.